Campaigning in Quebec Municipal Elections: When the Party Defines Door to Door Canvassing as “The Right Way” to Campaign - Mévellec, Anne (Frontiers in Political Science, 2021)
Electoral campaigns are one of the key moments in political life. Yet, there is little Canadian work on this subject when it comes to municipal elections. However, the European literature on campaigning provides an opportunity for useful questions on the transformations of this aspect of local political life by bringing together political sociology and electoral sociology. Several authors agree on the fact that electoral campaigns are getting rationalized, modernized and professionalized. However, an overly strategic conception of campaigns may lead to an overestimation of their professionalization. According to recent studies, campaigning is a more complex activity, made of technical devices and social interactions linked to the specificities of local contexts that structure political struggles. In this context, we present the results of an exploratory case study of campaigning in a municipal political party in a Canadian city, more specifically situated in the Province of Québec. Municipal political parties are usually considered as electoral machines. It is therefore important to study in detail the way these organizations conduct election campaigns. This exploratory work is based on the hypothesis that while parties try to impose a standard campaign model, candidates conform to it in various ways. Analysis of a series of semi-structured interviews with candidates and campaign managers will explore this paradoxical situation. This study of the design and conduct of an election campaign by a municipal political party in Quebec is, to our knowledge, the first of its kind. The results of our analysis provides a better understanding of the work of campaigners and political organizers in Quebec.